Positive and negative emotional spirals in eWOM of new recreational sports: A case study on Nordic Walking - Marta Zurawik; Ulla Hakala; Birgitta Sandberg (Inderscience Publishers, 2022)
Practising physical activities in public spaces may evoke a variety of emotional expressions, particularly when an activity is considered novel and embarrassing. To date, there is limited knowledge on emotional sharing concerning novel recreational activities in online context via electronic word-of-mouth (eWOM). We approach this knowledge gap by exploring online discussions on Nordic walking, the purpose being to investigate emotional sharing in online discussions concerning the activity. In our netnographic study, we analyse what kinds of discrete emotions related to Nordic walking are shared online in different countries, what the triggers of online emotional sharing are and what the outcomes expressed online by Nordicwalking practitioners are. We collected data from countries with various levels of Nordicwalking popularity and discovered four types of dynamics – negative spiral, positive spiral, positive change and negative change – that add to the research concerning emotional sharing.